IN VITRO FERTILIZATION DECISION-MAKING IN COUPLES WITH INFERTILITY: A LITERATURE REVIEW - Wahyuni, Eko Sari; Setyarini, Anggun (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Infertility is a reproductive health problem that affects couples of reproductive age in Indonesia. IVF offers hope for couples who have been waiting for a baby for a long time, but the decision needs to be carefully considered. The purpose of this literature review is to examine the factors that influence infertile couples' decision to choosen IVF. The method used in this study is literature review using databases from ProQuest, PubMed, Science Direct, and Google Scholar. The keywords used were